Liquid and peat inoculant, containing Azospirillum brasilense applied via seeds, is efficient in promoting growth and productivity in maize (Research, Society and Development, 2022)
It evaluated the performance of the liquid and peaty inoculant with (Azospirillum brasilense (Ab-V5 and Ab-V6), and nitrogen fertilization. Eight trials were carried out (February to August 2019), in four areas in the state of Paraná, in blocks at the random, with 7 treatments and 4 replications: There were four trials with liquid inoculant: T1 – control; T2 – 50% nitrogen dose; T3 – 100% nitrogen dose; T4 – 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 100 mL/60,000 seeds; T5 - 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 150 mL/60,000 seeds; T6 - 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 150 mL/60,000 seeds; T7 - 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 200 mL/60,000 seeds. Four trials with peaty inoculant: T1 – control; T2 – 50% nitrogen dose; T3 – 100% nitrogen dose; T4 – 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 100 g/60,000 seeds; T5 - 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 150 g/60,000 seeds; T6 - 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 150 g/60,000 seeds; T7 - 50% of nitrogen fertilization and inoculation of seeds with registered pattern, 200 g/60,000 seeds. The results confirm the agronomic efficiency of the liquid and peaty inoculants in maize, when used at a dose of 100 mL or 100 g/60,000 seeds, with half of the nitrogen fertilization recommended for the crop. With these dosages, yields were obtained significantly higher than the controls and treatments that received half the dose of nitrogen fertilizer without seed inoculation, being statistically similar to treatments with total nitrogen fertilization, to the standard inoculant.